Nonepileptic, Stereotypical, and Intermittent Symptoms (NESIS) in Patients With Subdural Hematoma: Proposal for a New Clinical Entity With Therapeutic and Prognostic Implications. Issue 1 (25th September 2019) - Levesque, Mathieu; Iorio-Morin, Christian; Bocti, Christian; Vézina, Caroline; Deacon, Charles
Abstract: BACKGROUND: Transient neurological symptoms (TNS) are frequent in patients with subdural hematomas (SDH) and many will receive a diagnosis of epilepsy despite a negative workup. OBJECTIVE: To explore if patients with TNS and a negative epilepsy workup (cases) evolved differently than those with a positive EEG (controls), which would suggest the existence of alternative etiologies for TNS. METHODS: We performed a single-center, retrospective, case-control study of patients with TNS post-SDH. The demographics and clinical and semiological features of cases and controls were compared. The outcome and response to antiepileptic drugs were also assessed and a scoring system developed to predict negative EEG. RESULTS: Fifty-nine patients with SDH-associated TNS were included (39 cases and 20 controls). Demographic characteristics were comparable in both groups. Dysphasia and prolonged episodes were associated with a negative EEG. Clonic movements, impaired awareness, positive symptomatology, complete response to antiepileptic drugs, and mortality were associated with a positive EEG. Using semiological variables, we created a scoring system with a 96.6% sensitivity and 100% specificity in predicting case group patients. The differences observed between both groups support the existence of an alternative etiology to seizures in our case group. We propose the term NESIS (NonEpileptic, Stereotypical, and Intermittent Symptoms) to refer to this subgroup and hypothesize that TNS in these patients might result from cortical spreading depolarization. CONCLUSION: We describe NESIS as a syndrome experienced by SDH patients with specific prognostic and therapeutic implications. Independent validation of this new entity is now required.